Does Grammatical Aspect Affect Motion Event Cognition? A Cross‐Linguistic Comparison of English and Swedish Speakers. (24th October 2012) - Athanasopoulos, Panos; Bylund, Emanuel
Abstract In this article, we explore whether cross‐linguistic differences in grammatical aspect encoding may give rise to differences in memory and cognition. We compared native speakers of two languages that encode aspect differently (English and Swedish) in four tasks that examined verbal descriptions of stimuli, online triads matching, and memory‐based triads matching with and without verbal interference. Results showed between‐group differences in verbal descriptions and in memory‐based triads matching. However, no differences were found in online triads matching and in memory‐based triads matching with verbal interference. These findings need to be interpreted in the context of the overall pattern of performance, which indicated that both groups based their similarity judgments on common perceptual characteristics of motion events. These results show for the first time a cross‐linguistic difference in memory as a function of differences in grammatical aspect encoding, but they also contribute to the emerging view that language fine tunes rather than shapes perceptual processes that are likely to be universal and unchanging.